2021
DOI: 10.1038/s41398-021-01244-7
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking behaviors and the importance of ethnicity and genetic ancestry

Abstract: Cigarette smoking contributes to numerous diseases and is one of the leading causes of death in the United States. Smoking behaviors vary widely across race/ethnicity, but it is not clear why. Here, we examine the contribution of genetic ancestry to variation in two smoking-related traits in 43,485 individuals from four race/ethnicity groups (non-Hispanic white, Hispanic/Latino, East Asian, and African American) from a single U.S. healthcare plan. Smoking prevalence was the lowest among East Asians (22.7%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…In the adjusted model, binary logistic regression results showed a significant positive association between tobacco consumption with the older age group (20)(21)(22)(23)(24), lower level of education, being married, and having a smoking parent. Whereas significant but negative correlation was found between young females and tobacco use behavior.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In the adjusted model, binary logistic regression results showed a significant positive association between tobacco consumption with the older age group (20)(21)(22)(23)(24), lower level of education, being married, and having a smoking parent. Whereas significant but negative correlation was found between young females and tobacco use behavior.…”
Section: Resultsmentioning
confidence: 93%
“…The explanatory variables were chosen based on the current literature, which identifies age, sex, level of education attained [6], [13] marital status [17], religion [18], ethnicity [20], access to the internet [21], and parental smoking behavior [23] as an important risk factor. To meet the requirements for binary logistics regression, all the independent variables were transformed into categorical ones.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…African ancestry and Asian ancestry were associated with decreased smoking intensity and nicotine metabolism measures in Pharmacogenetic Study participants. Ancestry within selfidentified ethnic strata was examined for association with CPD in non-treatment seeking ever smokers from a health maintenance organization (mean(SD) 55( 11) years of age and 58% female) 41 . Within group association of the first two geographically interpretable principal components of genetic variation was observed in non-Hispanic White (N=12898, 13% current), in East Asian (N=921, 15% but not in African American (N=554, 24% current) ever smokers.…”
Section: Smoking Measures Omb Race and Ancestrymentioning
confidence: 99%
“…Racial/ethnic group identities such as Black, White, Hispanic, Native American, East Asian and South Asian show empirically strong linkages to medical and behavioral traits such as obesity (Wang et al 2007), type 2 diabetes (Cheng et al 2013), hypertension (Lackland 2014), asthma (Choudry et al 2006), neuropsychological performance (Llibre-Guerra et al 2018), smoking behaviors (Choquet et al 2021), and sleep disorders (Halder et al 2015). An important research question is to what degree any such observed trait variation arises from differences in the typical diets, cultural practices and other environmental particularities of the racial/ethnic groups, or from similarity in genetic pools within each group traceable to shared geographic ancestry.…”
Section: Introductionmentioning
confidence: 99%